2022
DOI: 10.1002/mame.202200009
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite/Chitosan/Gelatin Films: Preparation, Supercritical CO2 Processing, Characterization, and Bioactivity

Abstract: Chitosan/gelatin and chitosan/gelatin/zeolite films prepared by solvent casting method are impregnated with a mixture of thymol and carvacrol using a green solvent, supercritical carbon dioxide at 35 °C and 30 MPa, during 18 h. Proposed method enables preparation of biocompatible and biodegradable blends with strong antioxidant and antibacterial activity, whereby amounts of loaded thymol/carvacrol (TC) mixture are in the range from 3.3% to 6%. After initial burst release, both types of films exhibit gradual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Conversely, the film materials containing zeolite alone did not exhibit significant antimicrobial efficacy. This finding aligns with those in the existing literature, which reports the lack of inherent antibacterial activity exhibited by zeolite itself [41,42].…”
Section: Antibacterial Properties Of Cs/pvoh/xnz and Cs/pvoh/xto@nz F...supporting
confidence: 93%
See 1 more Smart Citation
“…Conversely, the film materials containing zeolite alone did not exhibit significant antimicrobial efficacy. This finding aligns with those in the existing literature, which reports the lack of inherent antibacterial activity exhibited by zeolite itself [41,42].…”
Section: Antibacterial Properties Of Cs/pvoh/xnz and Cs/pvoh/xto@nz F...supporting
confidence: 93%
“…Similarly, Pajnik et al (2022) [42] reported analogous findings regarding the antibacterial effects of zeolite/chitosan/gelatin films. They observed that the antibacterial effect of the films alone, without thymol or carvacrol impregnation, was insignificant.…”
Section: Antibacterial Properties Of Cs/pvoh/xnz and Cs/pvoh/xto@nz F...mentioning
confidence: 62%
“…The functional groups of the nanofibers were analyzed via FT-IR (Figure a). Absorption peaks at 1090and 805 cm –1 assigned to Al–O and Si–O groups could be seen in the curves of Ze, Gel@Ze, and Gel@Ze@PDA, which were associated to the presence of zeolite. , The strong absorption peaks near 3420 cm –1 were identified as the −OH and −NH stretching of gelatin, and the absorption peaks at 1545 and 1240 cm –1 could be assigned to N–H/C–N stretching (amide II) and N–H bending (amide III), respectively. , It should be noted that no noticeable difference was found in the curves of Gel@Ze and Gel@Ze@PDA due to their similar characteristic peaks and low PDA content. Meanwhile, TG analysis also confirmed the presence of zeolite powders.…”
Section: Resultsmentioning
confidence: 96%
“…The unique properties of scCO2 and the environmental benefits of scCO2-assisted processes have led to a variety of its applications. ScCO2 processes on a laboratory scale are mostly used for (a) separation of bioactive extracts from plant material (4,6) to avoid the use of organic solvents and/or high temperatures (7), (b) supercritical drying to remove liquids from gels without a change in the wet gel matrix (8,9), (c) polymer impregnation with bioactive components (10,11), (d) both natural and synthetic textile dyeing (7), (e) modification/functionalization of inert inorganic solids (12), and (f) distribution of drugs into solid polymer matrices (13)(14)(15). In the field of polymeric processing, scCO2 can act as a plasticizer of semicrystalline and amorphous polymers and induce polymer foaming (16).…”
Section: The Versatility Of Supercritical Carbon Dioxidementioning
confidence: 99%